ABC architecture: a new approach to build reusable and adaptable business tier components based on static business interfaces - Pereira, Óscar M. (2013)
Currently, programmers of database applications use standard API and frameworks as artifacts to develop business tiers aimed at integrating the object-oriented and the relational paradigms. These artifacts provide programmers with the necessary services to develop business tiers. In this paper we propose a new architecture based on general Call Level Interfaces from which reusable and Adaptable Business tier Components (ABC) may be developed. Each individual ABC component is able to manage SQL statements of any complexity, deployed at run-time, and also to provide tailored services to each SQL statement. To accomplish this goal, the only requirement is that the schema of each deployed SQL statement must be in conformance with one of the pre-defined static schemas (interfaces) of the recipient ABC component. The main contributions of this paper are threefold: 1) to present the new architecture based on general Call Level Interfaces on which ABC components are based, 2) to show that the source code of ABC components may be automatically built by a tool and 3) to present a concrete example of ABC based on JDBC. The main outcome of this paper is the evidence that the presented architecture is an effective approach to build reusable and adaptable business tiers components to bridge the object-oriented and the relational paradigms.